AN ANALYSIS OF WORD STRESS IN THE NEWS READING VIDEOS OF PUBLIC RELATIONS STUDENTS - Maria Ulfah; Sari Rejeki; Henny Suharyati (Journal Albion : Journal of English Literature, Language, and Culture, 2022)
This study aims to analyze word stress and factors that cause the differences in pronunciation in the news reading videos of students majoring in Public Relations. Using the descriptive method, this study focuses on how students pronounce words stress by comparing the pronunciation with Standard American English (SAE). Through the transcription of the news reading, it is found that there are 30 words containing word stress. Working with 10 selected informants, results reveal that the students can pronounce 16 words with the correct stress. 11 words are pronounced in different syllables and 1 word is pronounced without stress. The rest of the data indicates diverse answers by the informants but still highlights the mispronunciation. The factors that cause difficulties in the pronunciation of word stress in English are the interferences of the mother tongue, the inconsistency of some sounds in English, the differences in phonological rules between English and Indonesian, and lastly, the lack of exposure to English as a medium for communication.Keywords: pronunciation; word stress; syllables.